KARAKTERISTIK NUGGET IKAN YANG DIPERKAYA DENGAN DAUN BELUNTAS (Pluchea indica L.) SEBAGAI PANGAN FUNGSIONAL - Susanto, Andri; Syska, Kavadya; Ropiudin, Ropiudin; Nurhayati, Asti Dewi; Istiqomah, Kholifatun; Aulia, Risfa; Hakim, Ahmad Luqman; Estiningrum, Diyah Palupi; Maskuri, Khasan; Najib, Akmal Auladi; Insani, Choerul; Subekti, Ilyas; Qodriyah, Laelatul; Ayuningtyas, Syella Aditya; Alfiana, Yulia Eva; Sukesi, Rina; Zahroh, Inarotul; Pranoto, Restu Aji Saripwijaya (Jurnal Agritechno, 2024)
Functional food products have garnered significant attention, particularly among individuals seeking both palatable and nutritionally enriched dietary options. Among these, fish nuggets, as a processed fish product, emerge as a promising candidate for fulfilling daily nutritional requirements. This research aims to explore the quality characteristics of fish nuggets enriched with beluntas leaves and assess the fat and protein content, positioning them as functional food products. The research adopted a Completely Randomized Design (CRD) with two factors: beluntas leaves and mackerel, each featuring three distinct treatments. Beluntas leaf concentrations comprised 10%, 20%, and 30%, while mackerel concentrations included 90%, 80%, and 70%. Data analysis utilized Analysis of Variance (ANOVA), with subsequent application of the Duncan 5% test if significant treatment effects were observed. Results indicated that the most effective treatment for protein content was I1BI, exhibiting an average value of 88.66%. Meanwhile, the I1B3 treatment yielded the optimal fat content, averaging at 0.161%. This suggests that elevating the percentage of beluntas addition positively correlated with increased crude protein content, while significantly reducing fat content. This research contributes valuable insights into formulating fish nuggets with the incorporation of beluntas leaves as functional food. The outcomes serve as a foundational platform for advancing the development of functional food products based on fish, offering not only diverse flavors but also enhanced nutritional value. Such innovations align with the growing demand for healthier food alternatives and underscore the potential of fish-derived functional foods to address nutritional deficiencies and promote overall well-being.